2013
DOI: 10.1055/s-0033-1347349
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa abnormalities in high-risk term infants: Comparison of ultrasound and MRI

Abstract: Objectives We aimed to assess the characteristics of posterior fossa (PF) abnormalities in a cohort of high-risk term neonates, as well as the diagnostic performance of cranial ultrasound (CUS) with additional mastoid fontanelle (MF) views for the detection of these abnormalities, with magnetic resonance imaging (MRI) being the reference standard. Methods In this retrospective study, 113 term neonates with CUS and subsequent MRI were included. Sensitivity, specificity, and predictive values of routine CUS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, a wide array of developmental disorders such as Chiari and Dandy Walker malformations and corpus callosum agenesis/dysgenesis, as well as vascular anomalies such as vein of Galen aneurysmal malformation, ventriculomegaly, and migrational abnormalities can also be revealed [8]. Detection of posterior fossa pathologies has been greatly enhanced by the addition of posterior and mastoid fontanel views to the standard anterior fontanel approach [9,10]. Cranial US has many roles in evaluating patients when there is a concern for neonatal HII.…”
mentioning
confidence: 99%
“…In addition, a wide array of developmental disorders such as Chiari and Dandy Walker malformations and corpus callosum agenesis/dysgenesis, as well as vascular anomalies such as vein of Galen aneurysmal malformation, ventriculomegaly, and migrational abnormalities can also be revealed [8]. Detection of posterior fossa pathologies has been greatly enhanced by the addition of posterior and mastoid fontanel views to the standard anterior fontanel approach [9,10]. Cranial US has many roles in evaluating patients when there is a concern for neonatal HII.…”
mentioning
confidence: 99%
“…The study showed that the additional examination via the MF increased the sensitivity, as well as the specificity, of the cranial ultrasound. 12 Recently, the same working group published a detailed description of the examination of the fossa posterior. 13 Specifically, in preterm infants, CUS has reached a new significance due to the possibility of detecting the smallest bleedings in the cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, the detection of posterior fossa hemorrhages by CUS may be difficult. 20 This is mainly due to the large distance between the AF and the posterior fossa. Despite this limitation, it is important to be aware that there are very specific clues on the AF views that can raise the suspicion of a large infratentorial hemorrhage.…”
Section: Discussionmentioning
confidence: 99%